Przełamując tabu. O najwcześniejszych filmowych echach wydarzeń marcowych - PIETRZAK, MACIEJ (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Breaking the taboo. The earliest cinematic echoes of the March 1968 experienc The articles author tries to prove that the experience of March 1968 had a great influence on the Polish film industry. Through the examples of Marek Piwowskis “The Cruise”, Tadeusz Konwickis “How Far Away, How Near” and Andrzej Żuławskis “The Devil” the author proves that the memory of March 1968 became a part of Polish filmography very soon, in spite of the unfavorable conditions arising from the vigilance of state censorship.